The value of LH maximum level in predicting optimal oocyte yield following GnRH agonist trigger - Lee, William Hao-Yu; Lin, Kuan-Ting; Hsieh, Yun-Chiao; Kao, Tzu-Ching; Huang, Ting-Chi; Chao, Kuang-Han; Chen, Mei-Jou; Yang, Jehn-Hsiahn; Chen, Shee-Uan (Frontiers in Endocrinology, 2023)
Background Risk factors associated with a suboptimal response to Gonadotropin-releasing hormone (GnRH) agonists include a high or low body mass index (BMI), prolonged use of oral contraceptive pills, and low luteinizing hormone (LH) levels on either the start or trigger days of controlled ovarian stimulation (COS). However, this approach may increase the need for a dual trigger and may also result in a higher incidence of ovarian hyperstimulation syndrome (OHSS) in hyper-responders. We aimed to investigate whether the maximum LH level during stimulation can serve as a predictive factor for achieving an optimal oocyte yield using the GnRH agonist trigger alone. Methods We retrospectively reviewed all antagonist protocols or progestin-primed ovarian stimulation (PPOS) protocols triggered with GnRH agonist only between May 2012 and December 2022. Subjects were divided into three groups, depending on basal LH level and LH maximum level. The freeze-all strategy was implemented in all cycles: Group 1, consistently low LH levels throughout COS; Group 2, low basal LH level with high LH max level during COS; Group 3, consistently high LH levels throughout COS. The primary outcome was the oocyte yield rate. The secondary outcome includes the number of collected oocytes, suboptimal response to GnRH agonist trigger, oocyte maturity rate, fertilized rate, clinical pregnancy rate, ongoing pregnancy rate, and live birth rate. The pregnancy outcomes were calculated for the first FET cycle. Results Following confounder adjustment, multivariable regression analysis showed that Group 1 (cycles with consistently low LH levels throughout COS) remains an independent predictor of suboptimal response (OR: 6.99; 95% CI 1.035–47.274). Group 1 (b = −12.72; 95% CI −20.9 to −4.55) and BMI (b = −0.25; 95% CI −0.5 to −0.004) were negatively associated with oocyte yield rate. Patients with low basal LH but high LH max levels had similar clinical outcomes compared to those with high LH max levels through COS. Conclusions The maximum LH level during COS may serve as an indicator of LH reserve and could be a more reliable predictor of achieving an optimal oocyte yield when compared to relying solely on the basal LH level. In the case of hyper-responders where trigger agents (agonist-only or dual trigger) are being considered, we propose a novel strategy that incorporates the maximum LH level, rather than just the basal or trigger-day LH level, as a reference for assessing LH reserve. This approach aims to minimize the risk of obtaining suboptimal oocyte yield and improve overall treatment outcomes.